The Effects of Problem Solving on Students' Cognitive, Affective, and Psychomotor in Applied Mathematics - Sriatun, Sriatun; Ekohariadi, Ekohariadi; Sumbawati, Meini Sondang; Anistyasari, Yeni; Saphira, Hanandita Veda (National Dong Hwa University, 2024)
This study aims to ascertain the impact of problem solving on the knowledge, attitudes, and skills of pupils acquiring mathematics in Bojonegoro's technology and engineering vocational schools. In accordance with the study's objectives, the Structural Equation Modeling analysis revealed that the effect of problem solving on knowledge aspects of mathematics learning for Vocational High School students was significant, whereas the effect of problem solving on attitudes in mathematics learning at Vocational High Schools in technology and engineering was insignificant. whereas the effect of problem solving on talents is notably positive. The implication of this study is that the effect of problem solving in applied mathematics learning can enhance the cognitive abilities and skills of vocational high school students in the concentration of motorcycle business engineering expertise, and can assist mathematics teachers in integrating mathematics material with the concentration of student expertise in order to meet the learning needs of students.